EVALUASI PENGGUNAAN TROTOAR JALAN MADONG LUBIS TERHADAP PEJALAN KAKI - Mukhlisin, Zuhrial; Sihombing, Alexander Tuahta; Hamzah, Amir (Universitas Asahan, 2025)
This study aims to evaluate the geometric conditions and level of service (Level of Service/LOS) of sidewalks on Jalan Madong Lubis, Kisaran Timur District, Asahan Regency. Sidewalks are important facilities for pedestrians that function to provide safety, comfort, and smooth mobility. However, in the research area, sidewalks face various obstacles such as street vendors (PKL), illegal parking, and utilities that reduce their main function. The research method uses a descriptive quantitative approach with primary data collection through direct observation of sidewalk conditions and counting the number of pedestrians on several road segments for six days. Secondary data includes regulations and technical standards from the Minister of Public Works Regulation No. 03/PRT/M/2014 and the Indonesian Road Capacity Manual (MKJI) 1997. The analysis results show that the width of the sidewalk on Jalan Madong Lubis is only 1.3 meters, below the minimum standard of 1.5 meters. The level of service of sidewalks on segments A, B, and C is in category B to C, while segment D experienced a drastic decrease to LOS F because almost all of the sidewalk space is covered by street vendors. Physical obstacles and damaged surfaces contribute to reduced user comfort and safety. Recommendations are provided to improve the physical condition of sidewalks, regulate street vendor activity, and provide supporting facilities to enhance sidewalk service levels as safe and comfortable pedestrian spaces